Native and Artificial Reticuloplasmins Co-Accumulate in Distinct Domains of the Endoplasmic Reticulum and in Post-Endoplasmic Reticulum Compartments - Torres, Esperanza (American Society of Plant Physiologists, 2001)
We compared the subcellular distribution of native and artificial reticuloplasmins in endosperm, callus, and leaf tissues of transgenic rice (Oryza sativa) to determine the distribution of these proteins among endoplasmic reticulum (ER) and post-ER compartments. The native reticuloplasmin was calreticulin. The artificial reticuloplasmin was a recombinant single-chain antibody (scFv), expressed with an N-terminal signal peptide and the C-terminal KDEL sequence for retrieval to the ER (scFvT84.66-KDEL). We found that both molecules were distributed in the same manner. In endosperm, each accumulated in ER-derived prolamine protein bodies, but also in glutelin protein storage vacuoles, even though glutelins are known to pass through the Golgi apparatus en route to these organelles. This finding may suggest that similar mechanisms are involved in the sorting of reticuloplasmins and rice seed storage proteins. However, the presence of reticuloplasmins in protein storage vacuoles could also be due to simple dispersal into these compartments during protein storage vacuole biogenesis, before glutelin deposition. In callus and leaf mesophyll cells, both reticuloplasmins accumulated in ribosome-coated vesicles probably derived directly from the rough ER.